2020
DOI: 10.1111/1541-4337.12632
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cell wall polysaccharides and polyphenols: Effect of molecular internal structure

Abstract: Cell wall polysaccharides (CPSs) and polyphenols are major constituents of the dietary fiber complex in plant-based foods. Their digestion (by gut microbiota) and bioefficacy depend not only on their structure and quantity, but also on their intermolecular interactions. The composition and structure of these compounds vary with their dietary source (i.e., fruit or vegetable of origin) and can be further modified by food processing. Various components and structures of CPSs and polyphenols have been observed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 175 publications
(668 reference statements)
2
94
0
Order By: Relevance
“…A previous report indicated that complex of EGCG and methyl cellulose exhibited aggregated spherical particles (Patel et al., 2013). The morphology differences of three complexes might be due to the different physicochemical properties of selected small molecules, that is, chemical structure, functional groups, molecular weight, and mixture ratio (X. Liu et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…A previous report indicated that complex of EGCG and methyl cellulose exhibited aggregated spherical particles (Patel et al., 2013). The morphology differences of three complexes might be due to the different physicochemical properties of selected small molecules, that is, chemical structure, functional groups, molecular weight, and mixture ratio (X. Liu et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To identify the fine structural characteristic of DK-H, further fractionation by column chromatography, such as ion exchange and size exclusion, in addition to chemical and structural analyses, such as GC-MS, IR, and NMR, is needed in future studies [28]. Thermodynamic and spectral measurements, polymer particle tracking analysis, and microstructure observation are also required to identify the structural interaction between the GalA-rich polysaccharide and polyphenols in DK-H [29]. In addition, individual polyphenol composition in DK-H might be fully identified in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…(Poly)phenol polymers, which represent a large proportion of those ingested in the diet, are often intimately bound through hydrophobic and hydrogen bonds to plant cell wall matrix and therefore reach the colon in the form of (poly)phenolic fibers ( 235 , 236 ). A clear case of fiber-associated (poly)phenols are polymeric flavan-3-ols, whose fermentation leads to SCFA biosynthesis while releasing the so-called “non-extractable (poly)phenols” ( 237 , 238 ), thereby illustrating another example of trophic interactions in the gut environment.…”
Section: Trophic Interactions Influencing Microbial Ecology Upon (Poly)phenol-rich Food Intakementioning
confidence: 99%